2010
DOI: 10.1186/1471-2369-11-25
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the balANZ trial: A randomised controlled trial of low GDP, neutral pH versus standard peritoneal dialysis solution for the preservation of residual renal function

Abstract: BackgroundThe main hypothesis of this study is that neutral pH, low glucose degradation product (GDP) peritoneal dialysis (PD) fluid better preserves residual renal function in PD patients over time compared with conventional dialysate.Methods/DesignInclusion criteria are adult PD patients (CAPD or APD) aged 18-81 years whose first dialysis was within 90 days prior to or following enrolment and who have a residual GFR ≥ 5 ml/min/1.73 m2, a urine output ≥ 400 ml/day and an ability to understand the nature and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(33 reference statements)
0
27
0
Order By: Relevance
“…For example, the absence of beneficial effect in the randomized trial by Fan et al 15 could be explained by the fact that 91% of patients in the intervention group received Physioneal, which is reported to contain levels of 3-dexoyglucosone (70-161 mmol/L depending on dialysate glucose concentration 27 ) that are intermediate between those of the intervention group (42-60 mmol/L) and the control group (173-324 mmol/L) in this study. 28 An alternative explanation for a possible renoprotective benefit of biocompatible fluid is reduced peritonitis risk. Numerous studies previously demonstrated that peritonitis and/or its subsequent treatment with nephrotoxic antibiotics are major risk factors for residual renal function decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the absence of beneficial effect in the randomized trial by Fan et al 15 could be explained by the fact that 91% of patients in the intervention group received Physioneal, which is reported to contain levels of 3-dexoyglucosone (70-161 mmol/L depending on dialysate glucose concentration 27 ) that are intermediate between those of the intervention group (42-60 mmol/L) and the control group (173-324 mmol/L) in this study. 28 An alternative explanation for a possible renoprotective benefit of biocompatible fluid is reduced peritonitis risk. Numerous studies previously demonstrated that peritonitis and/or its subsequent treatment with nephrotoxic antibiotics are major risk factors for residual renal function decline.…”
Section: Discussionmentioning
confidence: 99%
“…28 This study was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12606000044527) and the study protocol was approved by ethics committees at all participating centers. All patients provided written informed consent before trial participation.…”
Section: Study Oversightmentioning
confidence: 99%
“…A detailed description of the study design and methodology has been previously published (17), as have the results of the main primary and secondary analyses (16,(18)(19)(20)(21) The primary clinical outcome measure was number of episodes of a composite CVE as defined previously (20). A secondary clinical outcome measure was all-cause mortality during the study duration.…”
Section: Study Populationmentioning
confidence: 99%
“…A detailed description of the study design and methodology has previously been published (23), as have the results of the main primary and secondary analyses (22,24,25). The trial was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12606000044527).…”
Section: Methodsmentioning
confidence: 99%